The Influence of Liquidity, Profitability, and Leverage on the Financial Distress of Transportation Companies on the IDX in 2021-2023 - Komang Ayuk Supriani; Luh Diah Citra Resmi Cahyadi; Ni Luh Sri Purnama Pradnyani (LPPM Universitas Dhyana Pura, 2025)
Financial difficulty is a condition when a company or individual faces serious financial distress and cannot meet their financial obligations. The main causes include a decline in income, increased debt, or management issues. Factors such as leverage, profitability, and liquidity are key influences on a company's financial health. This research utilized secondary data and a quantitative approach. The study population included 16 transportation companies listed on the Indonesian Stock Exchange (IDX) from 2021 to 2023. Purposive sampling was used to choose the sample with specific criteria, resulting in 48 samples being selected for the analysis. Data analysis was performed using multiple linear regression with SPSS version 24. The findings indicated that for transportation companies listed on the IDX between 2021 and 2023, leverage has a negative effect on financial distress. Conversely, liquidity and profitability were found to have a positive and significant effect on financial distress. Keywords: Liquidity, Profitability, Leverage, Financial Distress